2020
DOI: 10.1002/lsm.23316
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of 755‐nm Picosecond Laser, 755‐ and 532‐nm Nanosecond Lasers for Treatment of Café‐au‐Lait Macules (CALMs): A Randomized, Split‐Lesion Clinical Trial

Abstract: Background and Objectives Many types of lasers have been used to treat café‐au‐lait macules (CALMs) since the introduction of the selective photothermolysis theory. However, the efficacy and safety of picosecond lasers, compared with those of nanosecond lasers, have not been researched. To compare the efficacy and safety of 755 nm picosecond laser (PS‐755 nm), Q‐switched (QS) Alexandrite 755 nm nanosecond laser (QS‐755 nm), and QS Nd:YAG 532 nm nanosecond laser (QS‐532 nm) for treating CALMs. Study Design/Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 37 publications
1
18
0
1
Order By: Relevance
“…But 11 lesions treated with LFQS 1064‐nm laser and 7 treated with HFQS 755‐nm laser were included in the Tertile 3 group (3.67 ≤ VAS ≤ 4), suggesting that within 3 months, the LFQS 1064‐nm laser may help more patients achieve the top‐third of efficacy. In our study, five patients (25%) showed significantly different responses to these two types of laser treatments (VAS difference of ≥1 between the efficacy of the two laser treatments), suggesting that the choice of laser type for subsequent treatment should depend on the results of initial test patches, which is consistent with our previous conclusions 3 . There may be two reasons why lesions can be removed by LFQS 1064‐nm laser treatment: irradiation of the target lesion by repetitive laser pulses can lead to cumulative effects that can be tailored to attain complete targeted ablation with minimal damage, 18 and the rate of melanosome regeneration is delayed in cells irradiated with the LFQS 1064‐nm Nd: YAG laser 19 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…But 11 lesions treated with LFQS 1064‐nm laser and 7 treated with HFQS 755‐nm laser were included in the Tertile 3 group (3.67 ≤ VAS ≤ 4), suggesting that within 3 months, the LFQS 1064‐nm laser may help more patients achieve the top‐third of efficacy. In our study, five patients (25%) showed significantly different responses to these two types of laser treatments (VAS difference of ≥1 between the efficacy of the two laser treatments), suggesting that the choice of laser type for subsequent treatment should depend on the results of initial test patches, which is consistent with our previous conclusions 3 . There may be two reasons why lesions can be removed by LFQS 1064‐nm laser treatment: irradiation of the target lesion by repetitive laser pulses can lead to cumulative effects that can be tailored to attain complete targeted ablation with minimal damage, 18 and the rate of melanosome regeneration is delayed in cells irradiated with the LFQS 1064‐nm Nd: YAG laser 19 .…”
Section: Discussionsupporting
confidence: 91%
“…There is no significant difference in the recurrence rate between the two laser treatments. After HFQS 755‐nm laser treatment, 65% of patients ( n = 13) experienced temporary hypigmentation, and the average remission time was 8 weeks (range 2−12 weeks), more than in previous studies (0%−2.44%) 3,22 . Follow‐up visits may not have been frequent enough in previous studies, resulting in a lack of relevant records 3,22 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Melanosis' elimination for cosmetic reasons is a common request in aesthetic dermatology [1][2][3][4]. Hyperpigmentations can be described as the darkening of the skin secondary to melanin increasing in skin layers.…”
Section: Introductionmentioning
confidence: 99%